Genetic association between circulating selenium level and the risk of schizophrenia in the European population: A two-sample Mendelian randomization study - Deng, Ming-Gang; Cui, Han-Tao; Nie, Jia-Qi; Liang, Yuehui; Chai, Chen (Frontiers in Nutrition, 2022)
Background The association between circulating the selenium level and the risk of schizophrenia remains unclear. Objective To determine the relationship between the circulating selenium level and the risk of schizophrenia, using the Mendelian Randomization method in the European population. Methods Single nucleotide polymorphisms (SNPs) associated with the circulating selenium level were identified at p < 5 × 10−8. The inverse variance weighted (IVW) method was used as the principal MR analysis, and MR Egger, weighted median, and MR PRESSO were used to determine the accuracy of IVW results. The Cochran's Q-test and Leave-One-Out sensitivity analysis were performed to evaluate the heterogeneity and stability of genetic variants on schizophrenia. Results The circulating selenium level was associated with decreased risk of schizophrenia by the IVW method (OR: 0.906, 95% CI:0.867–0.947). MR Egger, weighted median, and MR PRESSO methods got similar results. No heterogeneity was detected by the Cochran's Q-test, and no single SNP was driving the overall effect by leave-one-out analysis. Conclusion Our study provides support for the genetic relationship between the circulating selenium level and schizophrenia; the decreased circulating selenium level was associated with an elevated risk of schizophrenia.